Pengembangan Instrumen Tes Diagnostik Pilihan Ganda Tiga Tingkat (Three-Tier Test) Pada Pelajaran PAI di SD Negeri 03 Taman Agung Sumatera Selatan - Apriyadi Apriyadi; Zainul Hasan; Ade Rosad (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to describe the development process and qualitatively analyze the field-testing results of a three-tier multiple-choice diagnostic test instrument in Islamic Education (PAI). The core issue examined is the prevalence of pseudo-high scores caused by guessing techniques and latent misconceptions among students regarding abstract religious concepts. A descriptive qualitative approach was employed. Data were gathered through a combination of the three-tier diagnostic test (15 items), semi-structured interviews, participant classroom observations, and documentation review. Research participants were selected using a purposive sampling technique, comprising 25 fifth-grade students of SD Negeri 03 Taman Agung, South Sumatra, and two senior PAI teachers. Data analysis followed the Miles and Huberman interactive model. The findings revealed major themes, including